2014
DOI: 10.1111/btp.12156
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Frugivores With Different Foraging Behavior Can Show Similar Seed Dispersal Effectiveness

Abstract: Frugivores with disparate foraging behavior are considered to vary in their seed dispersal effectiveness (SDE). Measured SDEs for gibbons and macaques for a 'primate-fruit' were comparable despite the different foraging and movement behavior of the primates. This could help facilitate fruit trait convergence in diverse fruit-frugivore networks.Abstract in Thai is available in the online version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…By studying each frugivore, the relative contributions of each frugivore in seed dispersal can be assessed, which is important to understand the details of functional dispersal networks, such as the complementarity and redundancy between dispersal agents (McConkey et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By studying each frugivore, the relative contributions of each frugivore in seed dispersal can be assessed, which is important to understand the details of functional dispersal networks, such as the complementarity and redundancy between dispersal agents (McConkey et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Studying the relative contribution of individual fruit eaters to seed dispersal is important for understanding the complementarity or redundancy of dispersal agents in those networks (McConkey et al . , González‐Castro et al . ).…”
mentioning
confidence: 99%
“…The effectiveness of seed dispersal mutualisms has been widely explored in previous studies aiming to assess not only the immediate, but also the delayed effects frugivorous animals have on the plant populations they disperse (Schupp, ; Schupp et al., ). These studies have usually focused on the spatial patterns of seed deposition and seedling recruitment (Calviño‐Cancela & Martín‐Herrero, ; Escribano‐Ávila et al., ; Jordano & Schupp, ; McConkey et al., ; Rother, Pizo, & Jordano, ), whereas the temporal patterns of seed dispersal effectiveness during the fruiting phenophase have remained completely overlooked. Here, we fill this knowledge gap by demonstrating shifts in the identity and contribution of seed dispersers, the magnitude of seed rain (quantity component) and multiple demographic processes (quality sub components) necessary for seedling recruitment (quality component).…”
Section: Discussionmentioning
confidence: 99%
“…The location of the feeding trees was also recorded by a handheld GPS. On Kinkazan Island, cheek pouch dispersal by the macaques [Tsujino & Yumoto, 2009;McConkey et al, 2014] was rarely observed ; therefore, we did not consider this type of dispersal in this study.…”
Section: Ranging Of the Macaquesmentioning
confidence: 99%